Isolation of Low-Abundant Bacteroidales in the Human Intestine and the Analysis of Their Differential Utilization Based on Plant-Derived Polysaccharides - Tan, Huizi; Zhao, Jianxin; Zhang, Hao; Zhai, Qixiao; Chen, Wei (Frontiers in Microbiology, 2018)
Bacteroidales are the most abundant gram-negative bacteria flourished in the human intestine with great underlying benefits to be discovered and developed as the next-generation probiotics. However, the traditional isolation method limits the mining of low-abundant species. In this study, modified selective medium was established using xylan as the sole carbohydrate source to enrich low-abundant species such as Prevotella copri and Bacteroides xylanisolvens from healthy human fecal samples. The growth rate, transcriptomics, and metabolomics profiles of the enriched low-abundant species were then evaluated. The considerable upregulated genes encoding xylan-associated hydrolysis and transportation, along with the increased xylose production detected in the culture of the enriched Bacteroidales strains based on xylan, were considered as positive proof of the feasibility of the modified methodology.